PEMBUKAAN KEMBALI PERPUSTAKAAN DI ERA NEW NORMAL - ROCHANI NANI RAHAYU; AHMAD SAEFUDIN SURIAPERMANA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
A study using a survey method was conducted on librarians of the Indonesian Institute of Sciences (LIPI) with the aim of finding out what things they think need to be prepared if a library is reopened in the new era. It is known that all LIPI librarians are 53 people, with 38 expert librarians (71,70%) and 15 (28,30%) skilled librarians. A total of 31 questions were ask to them via Google form with a deadline for filling out 20-27 June 2020. It is known that 47 repondents answered questions. The collected data is presented in the form of a diagram, then a descriptive analysis and discussion, it can be concluded that more than 50% of the respondens agreedwith all the planning the time line for the reopening of the library, communicating to users about the services provided, limiting the number of visitors visiting, making arrangements for the course of transactions between users and librarians, library provide health detection equipment for librarians and visitors, and the most important is changes in the services by utilizing more internet based information technology. Therefore it is necessary to provide asource of information in digital form that can be accessed easily from various places wherever users are.